2018
DOI: 10.1021/acs.jafc.8b02487
|View full text |Cite
|
Sign up to set email alerts
|

Hapten-Grafted Programmed Probe as a Corecognition Element for a Competitive Immunosensor to Detect Acetamiprid Residue in Agricultural Products

Abstract: We have developed an effective competitive electrochemical immunosensor assay based on hapten-grafted programmed probe (HGPP) as a corecognition element for highly sensitive and selective detection of acetamiprid. Starting with the synthesis of hapten, HGPP was prepared using carboxyl group in the hapten and amino group in the 5' end of the programmed probe through covalent conjugation. Acetamiprid present in samples competes with HGPP to bind with capture antibody on the electrodes by specific recognition int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Therefore, chromatography‐based methods are unsuitable for in situ , nondestructive and rapid detection. In addition, immunoassay can be used as an alternative method for acetamiprid residue analysis, 9,10 but the method often lacks sensitivity and reproducibility and is expensive. Similarly, the immunology‐based approach is also not suitable for in situ and nondestructive detection.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, chromatography‐based methods are unsuitable for in situ , nondestructive and rapid detection. In addition, immunoassay can be used as an alternative method for acetamiprid residue analysis, 9,10 but the method often lacks sensitivity and reproducibility and is expensive. Similarly, the immunology‐based approach is also not suitable for in situ and nondestructive detection.…”
Section: Introductionmentioning
confidence: 99%
“…None of the potential interference pesticides showed considerable current change within a neonicotinoid reduction potential window of −1.18 to −1.24 V. The chosen herbicide species atrazine, glyphosate, dicamba, and 2,4-dichlorophenoxyacetic acid have become some of the most prevalent herbicides applied in the Midwest and pose threats of aerosolization and watershed contamination. , Additionally, the insecticides parathion and paraoxon were investigated as both have shown electroactive behavior between 0 and −0.4 V vs Ag/AgCl, a potential window that is inconsequential to the neonicotinoid sensing regime. Neonicotinoid studies to date have not reported a comprehensive pesticide interferent species analysis, as shown in Figure . ,, …”
Section: Resultsmentioning
confidence: 99%
“…Neonicotinoid studies to date have not reported a comprehensive pesticide interferent species analysis, as shown in Figure 4. 66,69,76 Finally, recovery tests were performed in water from the South Skunk River in the state of Iowa. The water was filtered through a 0.45 μm filter, brought to 0.5 M NaCl, and spiked with 40 μM of a neonicotinoid.…”
mentioning
confidence: 99%
“…Some examples of electrochemical immunosensors are reported for the detection of neonicotinoids [132,133], especially with aptamers [134,135] but in our knowledge, only one work has published on immunosensor for detection of acetamiprid [136]. This work is based on hapten-grafted programmed probe (HGPP) that competes with acetamiprid for the sites of an antibody-modified gold electrode (Figure 7).…”
Section: Immunosensors For Pesticide Determinationmentioning
confidence: 99%
“…( A ) Preparation of HGPP. ( B ) Competitive immunosensor assay for the detection of acetamiprid (reprinted with permission from [136]).…”
Section: Figurementioning
confidence: 99%